BRASSINOSTEROIDE E AUXINA NO DESENVOLVIMENTO E ENRAIZAMENTO INVITRO DE MIRTILEIRO (Vaccinium Ashei) - Oliveira, Marina Angelica de (2016)
The expansion of cultivated blueberry fields in Brazil is directly linked to the provision of quality seedlings to the market, which may result in the increase of production. The plant micropropagation technique enables the production and provides high quality plants, physiologically viable and healthy and free from viruses in a short space of time. Woody plants presente difficulty in the in vitro rooting, in this context the development of a more efficient system of rooting results in plants with higher physiological quality and reduction of losses during the acclimatization phase. In the first experimente the treatments consisted in 8 doses of BIOBRAS 16 (0; 0,1; 0,2; 0,3; 0,4; 0,5; 0,6; 0,7 mg L-1) added to the culture medium at the time of preparation. The following characteristics were evaluated: number of corns, callus diameter, number of roots, the total root length, total length, number of shoots, length of shoots, number of leaves and fresh mass. The lowest concentration of BIOBRAS 16 used (0,1 mg L-1) presented a higher percentage of rooting, root length and number of leaves, but also stimulated the development of calluses. The dose of 0,4 mg L-1 stimulated the formation of shoots and length thereof. There was no significant difference for other parameters evaluated. In the second experiment the treatments consisted in diferent doses of BIOBRAS 16 (0,1; 0,3; 0,5 mg L-1) associated to different doses of indole acetic acid (1; 3; 5 L-1 μM) added to the culture medium during preparation. The parameters evaluated were the same as the experiment 1. The use of BIOBRAS 16 associated with indolacetic acid showed a positive effect for the development of in vitro characteristics of blueberry. For rooting, the concentration of 0,3 mg L-1 BIOBRAS 16 + 5 μM AIA showed a higher percentage. Concentrations of 0,5 mg L-1 BIOBRAS 16 + 5 μM of AIA induced the formation and callus diameter, undesirable feature when the goal is rooting. For the parameters number of shoots and number of leaves, the best result was the concentration of 0,1 mg L-1 BIOBRAS 16 + 5 μM of AIA.